Inflation targeting as a shock absorber - Marcel Fratzscher; Christoph Grosse Steffen; Malte Rieth (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
We study the characteristics of inflation targeting as a shock absorber, using quarterly data for a large panel of countries. To overcome an endogeneity problem between monetary regimes and the likelihood of crises, we propose to study large natural disasters. We find that inflation targeting improves macroeconomic performance following such exogenous shocks. It lowers inflation, raises output growth, and reduces inflation and growth variability compared to alternative monetary regimes. This performance is mostly due to a different response of monetary policy and fiscal policy under inflation targeting. Finally, we show that only hard but not soft targeting reaps the fruits: deeds, not words, matter for successful monetary stabilization.
Keywords: E42; E52; E58; 330; Monetary Policy; Central Banks; Monetary Regimes; Dynamic Effects